SISTEM REKOMENDASI MAKANAN KHAS JAWA TENGAH BERBASIS APLIKASI TELEGRAM - Kurnia Widi Sutisna; Mardi Siswo Utomo (LPPM STMIK Lombok, 2021)
The Telegram application has a chatbot feature that can automatically send and receive messages to other users. Telegram chatbots can be linked to the recommendation system and make it easier for users to take advantage of the recommendation system anytime and anywhere. In the recommendation system that is built, users can search for food information that is being sought within the scope of Central Java. Users get information related to the food they are looking for through Telegram conversations. The recommendation system that is built makes it easy for users to be able to search for food with search parameters that can be adjusted according to user needs. The recommendation system was built using the Case Based Reasoning (CBR) method by calculating the similarities in analyzing the problem. The system can provide good recommendation results with an accuracy rate of 80%. The system can also adjust to the parameters given by the user. This system can also provide food details to be used as a reference for users in culinary searches.